Cell-cycle-dependent changes in ceramide levels preceding retinoblastoma protein dephosphorylation in G2/M. - Lee, J Y (1998)
Ceramide functions as a growth-inhibitory lipid-signalling molecule and might have a role in mediating the effects of extracellular agents on cell growth, differentiation and senescence. Here we investigate the roles of ceramide in cell cycle progression. With the use of the model of serum withdrawal, we were able to synchronize Wi-38 human diploid fibroblasts at different stages of cell cycle. Serum stimulation resulted in G0 to G1/S progression as determined by flow cytometric analysis and [3H]thymidine incorporation. Analyses of endogenous ceramide levels demonstrated that ceramide levels remained relatively constant on serum stimulation, indicating that ceramide might not be critical during G1/S transition. Treating exponentially growing Wi-38 human diploid fibroblasts with nocodazole led to cell cycle arrest at the G2/M phase of the cell cycle; 2 h after the removal of nocodazole, retinoblastoma (Rb) protein became dephosphorylated and the cells exited from G2/M and moved to the G1 phase of the new cycle. When cells were released from G2/M block by nocodazole, and before Rb protein dephosphorylation, endogenous ceramide levels transiently increased up to 2-fold at 0.5 h after the removal of nocodazole. Fumonisin B1, an inhibitor of ceramide synthase, inhibited the elevation of ceramide levels. Desipramine and SR33557, both acid sphingomyelinase inhibitors, did not have an appreciable effect on the elevation of ceramide levels. Furthermore, fumonisin B1 inhibited Rb protein dephosphorylation induced by endogenous ceramide but not by exogenous ceramide. These results demonstrate for the first time changes in ceramide during cell cycle progression and suggest that ceramide synthesized de novo might function as an endogenous modulator of Rb protein and cell cycle progression.